Principal Component Analysis in the Animal Products Precooling Process Using Compressive Type Plate Cooler - Surya Muttalib; Nursigit Bintoro; Joko Nugroho Karyadi; Arifin Dwi Saputro (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2025)
Precooling is a critical process in the post-harvest activities of vegetable and animal products. This research aimed to evaluate the relationship between animal products’ physical, mechanical, and chemical parameters and their relationship with the treatment combination of compressive force, cooling media, and type of animal product samples using a compressive type plate cooler. The research was carried out with three types of meat (beef, chicken, and fish), three compressive forces (0, 100, and 200 kg), and two types of cooling medium (ice cubes and dry ice). The results showed that PCA using XLSTAT could be used to reduce the number of parameters to two main components which could explain 75% of the total variation in the data set. PCA was able to group precooling treatments with cooling media based on the physical, chemical, and mechanical properties. Treatments using ice media for all types of meat and compressive forces were grouped in quadrants I and II, while those using dry ice media were grouped in quadrants III and IV. Based on the type of meat sample, the results of PCA were able to group beef and chicken samples in quadrants I and IV, while tuna fish samples were in quadrants II and III. Keywords: Animal product, Cooling medium, Force compression, P recooling, PCA.